Relationships between Cargo, Cell Penetrating Peptides and Cell Type for Uptake of Non-Covalent Complexes into Live Cells - Andrea-Anneliese Keller; Franziska Mussbach; Reinhard Breitling; Peter Hemmerich; Buerk Schaefer; Stefan Lorkowski; Siegmund Reissmann (MDPI AG, 2013)
Modulating signaling pathways for research and therapy requires either suppression or expression of selected genes or internalization of proteins such as enzymes, antibodies, nucleotide binding proteins or substrates including nucleoside phosphates and enzyme inhibitors. Peptides, proteins and nucleotides are transported by fusing or conjugating them to cell penetrating peptides or by formation of non-covalent complexes. The latter is often preferred because of easy handling, uptake efficiency and auto-release of cargo into the live cell. In our studies complexes are formed with labeled or readily detectable cargoes for qualitative and quantitative estimation of their internalization. Properties and behavior of adhesion and suspension vertebrate cells as well as the protozoa Leishmania tarentolae are investigated with respect to proteolytic activity, uptake efficiency, intracellular localization and cytotoxicity. Our results show that peptide stability to membrane-bound, secreted or intracellular proteases varies between different CPPs and that the suitability of individual CPPs for a particular cargo in complex formation by non-covalent interactions requires detailed studies. Cells vary in their sensitivity to increasing concentrations of CPPs. Thus, most cells can be efficiently transduced with peptides, proteins and nucleotides with intracellular concentrations in the low micromole range. For each cargo, cell type and CPP the optimal conditions must be determined separately.